Kebijakan Luar Negeri Sebagai Manifestasi Eksistensi Negara - Wibi Hambalie (Jurnal Sentris, 2017)
International relation can not be separated from state as the main actor. It is common for state to gain interest as much as it needs. Foreign policy becomes a way to communicate with another state. The state can use their foreign policy not only to communicate but also to show their manifestation and existance in the international system. Before producing a foreign policy, a state might want to prepare themselves in order to create a suitable policy for their people. Several factors like geographical position and demography or military strengh might influence the foreign policy. A decent foreign policy should reflect the will of the people. Foreign policy in the other way as a proof of existence could use a tool to deal with others